Development of quinoline-based theranostic ligands for the targeting of fibroblast activation protein - Lindner, Thomas; Loktev, Anastasia; Altmann, Annette; Giesel, Frederik L.; Kratochwil, Clemens; Debus, Jürgen; Jäger, Dirk; Mier, Walter; Haberkorn, Uwe (Journal of nuclear medicine, 2018)
Fibroblast activation protein (FAP) is overexpressed in cancer-associated fibroblasts and is involved in a variety of tumor-promoting activities such as matrix remodeling, angiogenesis, chemotherapy resistance, and immunosuppression. Because FAP shows low expression in most normal organs, it presents an interesting target for imaging and endoradiotherapy. In this investigation, FAP inhibitors (FAPIs) were modified and optimized for use as theranostic tracers. Methods: FAPIs based on a quinoline structure were synthesized and characterized with respect to binding, internalization, and efflux in cells expressing human and murine FAP as well as CD26. Preclinical pharmacokinetics were determined in tumor-bearing animals with biodistribution experiments and small-animal PET. Finally, a proof-of-concept approach toward imaging and therapy was chosen for 2 patients with metastasized breast cancer. Results: Of 15 synthesized FAPIs, FAPI-04 was identified as the most promising tracer for clinical application. Compared with the previously published ligand, FAPI-02, FAPI-04 showed excellent stability in human serum, higher affinity for FAP as opposed to CD26, and slower excretion in vitro. In vivo, a higher SUV was reached in tumor-bearing animals, leading to larger areas under the curve as calculated from biodistribution experiments. Finally, PET/CT scans with 68Ga-FAPI-04 in 2 patients with metastasized breast cancer revealed high tracer uptake in metastases and a reduction in pain symptoms after therapy with a considerably low dose of 90Y-FAPI-04. Conclusion: FAPI-04 represents a promising tracer for both diagnostic imaging and, possibly, targeted therapy of malignant tumors with a high content of activated fibroblasts, such as breast cancer.
Gesehen am 24.02.2020